(untitled) (Hoboken, N.J., 2007)
This unique volume describes how the interaction of molecules with toxicologically relevant targets can be predicted using computer-based tools utilizing X-ray crystal structures or homology, receptor, pharmacophore, and quantitative structure activity relationship (QSAR) models of human proteins. It covers the in vitro models used, newer technologies, and regulatory aspects. The book offers a complete systems perspective to risk assessment prediction, discussing experimental and computational approaches in detail.
Keywords: Toxicology,Toxicology,Độc chất học,Độc chất học; Mathematical models,Computer simulation,Mô hình toán học,Máy tính mô phỏng